Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the possible values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] such that [tex]\( x + y = 3 \)[/tex], we need to find pairs of whole numbers that add up to 3. Let's go through the process step-by-step:
1. Identify the equation: We have the equation [tex]\( x + y = 3 \)[/tex].
2. List out all whole numbers from 0 to 3 (inclusive) for [tex]\( x \)[/tex], since [tex]\( x \)[/tex] and [tex]\( y \)[/tex] must be whole numbers:
[tex]\[ x \in \{0, 1, 2, 3\} \][/tex]
3. Calculate corresponding [tex]\( y \)[/tex] values:
For each [tex]\( x \)[/tex] value, solve for [tex]\( y \)[/tex] by rearranging the equation [tex]\( y = 3 - x \)[/tex].
- When [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 3 - 0 = 3 \][/tex]
Thus, one pair is [tex]\((0, 3)\)[/tex].
- When [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 3 - 1 = 2 \][/tex]
Thus, another pair is [tex]\((1, 2)\)[/tex].
- When [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 3 - 2 = 1 \][/tex]
Thus, another pair is [tex]\((2, 1)\)[/tex].
- When [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 3 - 3 = 0 \][/tex]
Thus, the final pair is [tex]\((3, 0)\)[/tex].
4. List the possible pairs:
- [tex]\((0, 3)\)[/tex]
- [tex]\((1, 2)\)[/tex]
- [tex]\((2, 1)\)[/tex]
- [tex]\((3, 0)\)[/tex]
Therefore, three possible values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy [tex]\( x + y = 3 \)[/tex] are [tex]\( (0, 3) \)[/tex], [tex]\( (1, 2) \)[/tex], and [tex]\( (2, 1) \)[/tex]. In fact, these are all the possible pairs given our constraints.
1. Identify the equation: We have the equation [tex]\( x + y = 3 \)[/tex].
2. List out all whole numbers from 0 to 3 (inclusive) for [tex]\( x \)[/tex], since [tex]\( x \)[/tex] and [tex]\( y \)[/tex] must be whole numbers:
[tex]\[ x \in \{0, 1, 2, 3\} \][/tex]
3. Calculate corresponding [tex]\( y \)[/tex] values:
For each [tex]\( x \)[/tex] value, solve for [tex]\( y \)[/tex] by rearranging the equation [tex]\( y = 3 - x \)[/tex].
- When [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 3 - 0 = 3 \][/tex]
Thus, one pair is [tex]\((0, 3)\)[/tex].
- When [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 3 - 1 = 2 \][/tex]
Thus, another pair is [tex]\((1, 2)\)[/tex].
- When [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 3 - 2 = 1 \][/tex]
Thus, another pair is [tex]\((2, 1)\)[/tex].
- When [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 3 - 3 = 0 \][/tex]
Thus, the final pair is [tex]\((3, 0)\)[/tex].
4. List the possible pairs:
- [tex]\((0, 3)\)[/tex]
- [tex]\((1, 2)\)[/tex]
- [tex]\((2, 1)\)[/tex]
- [tex]\((3, 0)\)[/tex]
Therefore, three possible values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy [tex]\( x + y = 3 \)[/tex] are [tex]\( (0, 3) \)[/tex], [tex]\( (1, 2) \)[/tex], and [tex]\( (2, 1) \)[/tex]. In fact, these are all the possible pairs given our constraints.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.